O direito de acesso à informação desportiva como direito do jornalista - Duarte, Valter Jorge Rodrigues (2016)
In the present dissertation we will present the rights of Journalists in the exercise of their held position, with the purpose of ensuring the effectiveness of their rights on the matter of access to sports information, following the dictates of the Portuguese Constitution and other legislation about the social media sector. To achieve so, we propose for chapter I to develop themes as the concept of sports, its relevance, its’s constitutional relevance and the importance of sports journalism. For chapter II we develop themes such as the freedom of speech and information in general and specifically in relation to journalist’s rights, the journalist´s professional card and other cards and complementary tools that facilitate them on their held occupation in sports grounds, the concept of sports information, also the regulating answer issued by the Portuguese Professional Football Federation and buy the Portuguese Professional Football League on the matter of the conditions of access to sports information, the historical contribution of the Basic Law of Sports System, the right to access sports information and the right to sports events and shows. For chapter III we address themes such as the decisions of the Regulating Entity for Social Media (REC) on the matters of disputes between journalists and Football Clubs and finally the forms of responsibility.